Cálculo dos coeficientes de conversão de dose efetiva em termos de Kerma no ar para fótons utilizando simulador antropomórfico voxel masculino na postura sentada - Galeano, Diego Castanon (2013)
The dose limits are set in terms of protection quantities. However, these quantities are not directly measurable. Thus, it is necessary to calculate the dose conversion coefficients (CCs), which relate these protection quantities with measurable physical quantities. In this work, were calculated CCs for equivalent dose and effective dose in terms of air kerma in a male voxel simulator at standing and sitting postures in air and vacuum environments. The Visual Monte Carlo (VMC) code was used to develop irradiation scenarios with a plane source of monoenergetic photons with energy ranging from 0.01 MeV to 2.0 MeV for irradiation geometries anteroposterior (AP), postero-anterior (PA), left lateral (LLAT), right lateral (rlat) and rotational (ROT). In order to observe possible variations between the CCs calculated, these values were compared for each environment and each posture. Were also compared the values of CCs of the simulator in standing posture with the CCs presented in publications 74 and 116 of the ICRP. The comparison between the values of CCs obtained with the simulator in the standing posture used in this work and the values presented in publications 74 and 116 of the ICRP shows variations in practically all organs, due mainly to differences between the simulators used such as organs mass and anatomy. By comparing the CCs values in air and vacuum environments, variations were observed in the CCs up to 83% at low energies (energies below 0.05 MeV). These variations occur mainly in the AP irradiation geometry. There were also significant differences primarily in AP, PA and ROT irradiation geometries, with variations of up to 100% in the CCs between the two postures in 7 of the 18 organs studied. The comparison between the CCs for effective dose between the sitting and standing posture showed differences in irradiation geometries AP, PA and ROT, with variations of up to 53 %. The divergences found in CCs between sitting and standing posture are attributed mainly to the difference in distribution and geometry of the organs when the posture of the simulator is modified. It is verified thus the importance of obtaining dose conversion coefficients using radiation scenarios in which the simulator are in different environments and postures than those found in the literature